1998
DOI: 10.1111/j.1399-6576.1998.tb05081.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemolysis following rapid experimental red blood cell transfusion

Abstract: Both the pumps used in this study are safe alternatives for rapid transfusion of RBCs; however, with MRP this can be accomplished approximately twice as fast as with the PIP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…Four publications (23.5%) noted significant statistical alterations in the outcome variables. However they opted on determining the presence of hemolysis being clinically significant for values where the level of hemolysis was above 0.8% 18 , 20 , 25 , 28 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four publications (23.5%) noted significant statistical alterations in the outcome variables. However they opted on determining the presence of hemolysis being clinically significant for values where the level of hemolysis was above 0.8% 18 , 20 , 25 , 28 .…”
Section: Resultsmentioning
confidence: 99%
“…The manufacturers ought to pay attention to the international standard in the International Organization for Standardization (ISO) 1135-4 38 , that determines the maximum pressure level for infusion at 40 kilopascal (kPa) 9 , 25 , 38 . No publication stated the value of the infusion pressure as a possible factor for cellular damage.…”
Section: Discussionmentioning
confidence: 99%
“…Not only is the mechanism of the pump relevant, other conditions can cause damage of cells during transfusion. Rapid transfusion in massive blood loss and very slow infusion rates in neonates results in a marginal increase of hemolysis, in particular, in older units 1,8,19,20 . Thompson and coworkers 8 also observed more hemolysis when a specific integral mesh filter was used, which was not seen when standard blood transfusion sets were used.…”
Section: Discussionmentioning
confidence: 99%
“…A potential disadvantage of this technique is that transfusion under conditions of extreme pressure may cause hemolysis of RBCs because of greater shear stress on the erythrocytes caused by the more turbulent blood flow through the transfusion set or by the direct pressure applied to the cells in the blood bag. Previous studies have shown that application of an external pressure device may result in increased hemolysis of transfused blood, but that this hemolysis is not clinically significant 2,3 . Others have recommended adding saline to the blood bag to decrease hemolysis when using a pressure device 4 .…”
mentioning
confidence: 99%